The Role of Portal Vein Thrombosis in the Clinical Course of Inflammatory Bowel Diseases: Report on Three Cases and Review of the Literature - Emanuele Sinagra; Emma Aragona; Claudia Romano; Simonetta Maisano; Ambrogio Orlando; Roberto Virdone; Lorenzo Tesè; Irene Modesto; Valeria Criscuoli; Mario Cottone (Gastroenterology Research and Practice)
Inflammatory bowel diseases are associated with an increased risk of vascular complications. The most important are arterial and venous thromboembolisms, which are considered as specific extraintestinal manifestations of inflammatory bowel diseases. Among venous thromboembolism events, portal vein thrombosis has been described in inflammatory bowel diseases. We report three cases of portal vein thrombosis occurring in patients with active inflammatory bowel disease. In two of them, hepatic abscess was present. Furthermore, we performed a systematic review based on the clinical literature published on this topic.